IMPLEMENTASI ASAS FUNGSI SOSIAL HAK ATAS TANAH DAN HUBUNGANNYA DENGAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - SANIAH . (JURNAL ILMIAH KOHESI, 2023)
The principle of the social function of land rights contained in article 6 of UUPA No. 5 of 1960, implies that in individual rights there are also community rights, the stronger the pressure from society or the public interest, the more individu interests must give away. The principle of the social function of land rights should not be interpreted as meaning that individual rights can be ignored for the sake of development. Therefore, in relation to land acquisition for the public interest, it is essentially the implementation of the principle of the social function of land rights. Still, the law states that for people whose land is taken by the government, the holder of land right rights is obliged to get proper and fair compensation.